Structure-Activity relationship of MDSA and its derivatives against Staphylococcus aureus Ser/Thr phosphatase Stp1. (April 2020) - Gao, Yawen; Wang, Guizhen; Wang, Xiyan; Yang, Yanan; Niu, Xiaodi
Graphical abstract: Highlights: Molecular modeling and binding free energy calculations were used. Met39, Ile163, Ile164, Val167 and Asp233 were key residues in the complexes. The structure-activity relation at the atomic level was determined. Abstract: Ser/thr phosphatase Stp1 is an important virulence factor for Staphylococcus aureus (S. aureus) and plays a key role in its infectivity, suggesting that it could serve as a potential target for treatment of S. aureus infection. Previous studies found that the activity of Stp1 was inhibited by MDSA and its derivatives. In this paper, we used molecular docking, molecular modeling, molecular dynamics simulations, binding free energy decomposition calculations, and hydrogen bond analyses to explore the structure-activity relationship. Energy decomposition indicated that MDSA, hydroxymethyl MDSA, carboxymethyl MDSA and methyl MDSA can bind to the catalytic pocket of Stp1. Furthermore, Met39, Ile163, Ile164, Val167, Gly195 and Asp233 were key residues in the Stp1-inhibitor complexes. Due to the lack of a double salicylate structure, salicylic acid cannot bind to the active site of Stpl, leading to loss of inhibitory activity. Based on these results, the structure-activity relationship at the atomic level was determined, which can promote the development of new and more effective anti-drug resistance inhibitors.